Reducing meat consumption with consumer insights and the nudge by proxy: the anomaly of asking, the power of protein, and illusions of insufficiency and availability - Macdonald, Chris (Frontiers in Sustainable Food Systems, 2025)
High global meat consumption presents significant environmental challenges. Interventions to reduce meat consumption, such as carbon labelling, have shown modest and inconsistent results, a phenomenon potentially explained by an “environmentalist bias.” This paper introduces and tests a consumer-centric “nudge by proxy” approach, which indirectly encourages choices that mitigate or obviate external costs by addressing consumers’ internal motivations. First, a consumer survey of 1,500 UK students identified “protein” as the most significant perceived barrier to adopting a meat-free diet. Subsequently, two choice experiments (N = 3,000) were conducted. Experiment 1 demonstrated that labelling the protein content significantly increased selection of the meat-free option over a meat-based counterpart when compared to both a control group (p < 0.001) and a carbon label group (p < 0.001). Experiment 2 confirmed the efficacy of the protein nudge, showing it had significantly increased the choice of a separate meat-free option by over 100% compared to a control group (p < 0.001). The paper concludes by discussing the importance of consumer engagement and addressing two illusions with future research: the “insufficiency illusion” whereby consumers falsely believe meat-free options to be lacking in a key area, and the “availability illusion,” when meat-free options are available but are genuinely lacking. The author advocates for a practical dual-pronged approach that both reveals and creates better options for the consumer.